2019
DOI: 10.1111/bju.14777
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spontaneous stone passage in a contemporary cohort of patients presenting with acute ureteric colic: results from the Multi‐centre cohort study evaluating the role of Inflammatory Markers In patients presenting with acute ureteric Colic (MIMIC) study

Abstract: stone size from a large contemporary cohort adjusting for key potential confounders. We anticipate that these data will aid clinicians managing patients with acute ureteric colic and help guide management decisions and the need for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 28 publications
5
34
1
Order By: Relevance
“…This study found that smaller stones were more likely to pass spontaneously when compared to larger stones (<5 mm 486/551 [87%], >5 mm 814/1,093 [75%]). These findings are similar to stones in other points of the urinary tract as Shah et al [6] recently demonstrated. One of our included studies concluded that stones were 3 times more likely to pass spontaneously if they were situated at the ureterovesical junction as opposed to any other part of the distal ureter [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that smaller stones were more likely to pass spontaneously when compared to larger stones (<5 mm 486/551 [87%], >5 mm 814/1,093 [75%]). These findings are similar to stones in other points of the urinary tract as Shah et al [6] recently demonstrated. One of our included studies concluded that stones were 3 times more likely to pass spontaneously if they were situated at the ureterovesical junction as opposed to any other part of the distal ureter [13].…”
Section: Discussionsupporting
confidence: 89%
“…A large, international, retrospective cohort study recently noted that distal ureteric stones are significantly more likely to pass with conservative management alone compared to stones situated more proximally in the ureter [6]. However, when counselling patients to trial conservative management of their stone, it is crucial to understand the natural history of these patients with respect to the time frame they can be observed for before attempting other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…• In children, ultrasound should be used as the first-line diagnosis imaging technique. and >7mm respectively 46 . For stones in the proximal and distal ureter the passage rates were 52% and 83%.…”
Section: Statementsmentioning
confidence: 97%
“…Urinary stones are a group of diseases that occupy the agenda of the medical world with both their frequency and high recurrence rates. 1 Over the last 60 years, great strides have been made in urinary stone treatment, and in the previous two decades, endoscopic surgeries have taken the lead in treatment. 2,3 Ureterorenoscopy (URS) and flexible ureterorenoscopy (fURS) are commonly used surgical methods in ureter stone treatment.…”
Section: Introductionmentioning
confidence: 99%